Nesting phenology and breeding success in great spotted woodpecker Picoides major near Warsaw (Central Poland) - Mazgajski, Tomasz D. (Muzeum i Instytut Zoologii PAN, 2002)
The study was carried out between 1996 and 1998 on a plot covered by mixed woodland near the southern boundary of the city of Warsaw. A total of 39 nests were investigated. The woodpeckers laid their eggs during the last ten days of April and at the beginning of May. The mean clutch size was 5.6 (n = 18). The number of young reared differed from season to season and was associated with the fledging date. More fledglings left nests with earlier broods. 81% of broods were successful, i.e. at least one young was reared. The duration of the breeding season - from the laying of the first egg to the fledging of the last chick - was 40-42 days.
Bibliogr. s. 4-5
5 s. : il. ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Keywords: Dzięcioł duży -- biologia lęgowa -- Polska -- Warszawa (region) [KABA]; terminy i wyniki lęgów; dzięciołowate; ptaki; Dendrocopos major; Picoides major; Picidae; Aves

Competition for nest sites between the starling Sturnus vulgaris and other cavity nesters - study in forest park - Mazgajski, Tomasz D. (Muzeum i Instytut Zoologii PAN, 2000)
Three species of cavity nesters potentially competitive with the Starling - the Great Spotted Woodpecker Dendrocopos major, Middle Spotted Woodpecker D. medius and Nuthatch Sitta europaea were studied in the years 1997-1999 in the M3ociny forest park, Warsaw, Poland. The number of suitable nest sites for Starlings and competitive pressure were manipulated by increasing or decreasing the availability of nest boxes. Increased nest-site competition did not lead to significant changes in number among the studied species. The Starling was found to take over up to 25% of holes chosen by Nuthatches for breeding. Increased availability of nest sites did not protect Nuthatches from cavity losses, but reduced their frequency. Only 20% of Nuthatch pairs that lost their holes renested successfully in the same breeding season. No impact of Starlings on breeding woodpeckers was noted. Differences in Starling competitive pressure between Europe and North America are discussed.
Referat wygłoszony na Second Meeting of the European Ornithologists' Union
Bibliogr. s. 106-107
S. [103]-107 ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Keywords: Szpak -- Polska -- Warszawa -- konferencje [KABA]; Dziuplaki -- Polska -- Warszawa -- konferencje [KABA]; Park Młociński; miejsca gniazdowe; konkurencja; szpakowate; ptaki; Sturnus vulgaris; Sturnidae; Aves

Amphibians of Poland's urban areas - Mazgajska, Joanna; Mazgajski, Tomasz D. (Museum and Institute of Zoology, PAS, 2010)
Z wielu powodów urbanizacja działa niekorzystnie za płazy. Dlatego też zwierzęta te wycofują się ze środowiska miejskiego, zmniejszając tu swoją liczebność lub wręcz całkowicie zanikając. Dane dotyczące batrachofauny zamieszkującej miasta są niewystarczające, co uniemożliwia podjęcie skutecznych działań ochronnych wobec tej grupy zwierząt. Dlatego też tak istotne dla określenia mechanizmów zanikania płazów na terenach zurbanizowanych było zebranie i usystematyzowanie według spójnej metodyki wyników badań płazów z 9 polskich miast (Białystok, Gniezno, Lublin, Olsztyn, Oława, Słupsk, Wałbrzych, Wrocław i Zielona Góra). Na terenach badań stwierdzono w sumie 13 gatunków płazów plus mieszańca hybrydogenetycznego - żabę wodną Rana kl. esculenta Linnaeus, 1758. W poszczególnych miastach stwierdzano od 9 do 13 taksonów. Brak pozostałych gatunków płazów wschodzących w skład polskiej batrachofauny związany jest najprawdopodobniej wyłącznie z przebiegiem ich zasięgów geograficznych.Zebrane w monografii publikacje mogą stanowić punkt wyjścia do szerzej zakrojonych badań płazów na terenach polskich miast oraz do podjęcia właściwych działań ochronnych, które pozwolą na zachowanie ich populacji w tym nieprzyjaznym dla nich środowisku.
Bibliogr. przy artykułach
S. [1], 117-125 : il. (w tym kolor.) ; 25 cm
Streszcz. ang., pol. Nazwy taksonów również łac.
Keywords: Płazy -- rozmieszczenie geograficzne -- Polska [KABA]; Płazy -- Polska [KABA]; Płazy -- populacje -- Polska [KABA]; Płazy -- skutki działalności człowieka -- Polska [KABA]; Zwierzęta miast -- Polska [KABA]; Amphibia; batrachofauna; żaby; ropuchy; traszki; antropopresja; urbanizacja; zmiany siedliskowe

Cross-species amplification of microsatellite loci in European woodpeckers (Picidae) - Rutkowski, Robert; Mazgajski, Tomasz D.; Rejt, Łukasz (Fundacja Natura optima dux, 2006)
Microsatellites are currently a popular genetic marker in population and conservation genetics. Initial identification of the marker is expensive and labour-consuming, therefore cross-species microsatellite amplification is often use in species witha poorly recognized genome. The aim of our study was to assess the possibility of using microsatellite markers described for white-backed woodpecker Dendrocopos leucotos ingenetic studies of other species of European Picidae. The set of six microsatellites wastested on nine woodpecker species. For each of them we describe number of loci successfully amplified and their level of polymorphism. We briefly discuss the possibility of utilizing tested markers in population and ecological studies of Picidae.
Bibliogr. s. 825-826
S. 819-826 ; 27 cm
Nazwy taksonów w jęz. łac.
Keywords: woodpeckers; Picidae; microsatellites; cross-species amplification; Dendrocopos; Picus; Picoides; Dryocopus; Jynx

Mitochondrial marker for studying European Picidae at various taxonomic levels - Rutkowski, Robert; Jagołkowska, Patrycja; Mazgajski, Tomasz D.; Rejt, Łukasz (Natura optima dux Foundation, 2008)
Genetic data has tremendously deepen our knowledge of evolutionary history of populations and species as well as ecology and biology of the species. Appropriate molecular markers allow researchers to gain an insight into distribution of genetic diversity, starting from characterization of single individual, through description of processes having an influence on natural populations, to phylogenetic relationships among higher taxonomic units. Woodpeckers (Aves: Picidae) are especially sensitive to anthropogenic habitat changes, such as forest transformation resulting from silvicultural practices. As such they have been regarded as good biological indicators of forest biodiversity and therefore may play an important role as a model species in conservation biology. To broaden our understanding of woodpeckers' evolution, biology and ecologymolecular techniques needs to be applied. Here, we developed pair of degenerate primersfor amplification of hypervariable domain of mtDNA control region in wide range of European Picidae. High level of polymorphism of obtained sequences in majority of species indicate that amplified region will be very useful to study phylogeny, population genetics and phylogeography of the family.
Bibliogr. s. 912-913
S. 907-913 ; 27 cm
Nazwy taksonów w jęz. łac.
Keywords: mtDNA; control region; woodpeckers; degenerate primers; molecular markers

Influence of the nest-site size on nestlings' condition, the case of starling Sturnus vulgaris - Kędra, Aleksander H.; Mazgajski, Tomasz D.; Kowalczyk, Krzysztof (Muzeum i Instytut Zoologii PAN, 1999)
Nestlings' condition parameters (body weight, tarsus and wing length) of Starling breeding in nest-boxes of various sizes were studied during two years. Two types of nest-boxes were used: normal - typical for that species, (bottom size 195 cm2, depth 22 cm) and 20-25% smaller. It was found that Starling didn't adjust their clutches to nest-box size. Also number of fledgelings was not related to nest-box size. Significant differences between nestling development in normal and smaller nest-boxes were found only during the first days of life, when nestling growth is intensive. In older stages of nestlings development those diferences dissappeared.
Referat wygłoszony na Second Meeting of the European Ornithologists' Union
Bibliogr. s. 207-208
S. [205]-208 ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Keywords: Szpak -- młode -- Polska -- Warszawa -- konferencje [KABA]; Park Młociński; kondycja piskląt; wielkość miejsca gniazdowego; szpakowate; ptaki; Sturnus vulgaris; Sturnidae; Aves; 1996-97

Fleas Siphonaptera influence the condition of starling Sturnus vulgaris nestlings - Mazgajski, Tomasz D.; Kędra, Aleksander H.; Modlińska, Ewa; Samborski, Jarosław (Muzeum i Instytut Zoologii PAN, 1997)
Bibliogr. s. 189
S. [185]-190 ; 27 cm
Streszcz. pol.
Keywords: Szpak -- młode -- pasożyty -- Polska -- Warszawa [KABA]; Pchły [KABA]; Parki miejskie -- Polska -- Warszawa [KABA]; Park Młociński; kondycja piskląt; ektopasożyty; owady; szpakowate; ptaki; 1996; Siphonaptera; Aphaniptera; Insecta; Sturnus vulgaris; Sturnidae; Aves

Amphibians of Białystok - Chętnicki, Włodzimierz; Siwak, Paweł; Mazgajska, Joanna; Mazgajski, Tomasz D. (Museum and Institute of Zoology, PAS, 2010)
W latach 1998-2000 przeprowadzono badania batrachofauny 100 zbiorników wodnych. Z tej liczby 87 zbiorników położonych było na terenie Białegostoku, zaś 13 w jego najbliższych okolicach, poza granicami administracyjnymi (do 2,5 km od nich). Zbiorniki rozrodcze płazów opisano biorąc pod uwagę wybrane cechy fizyczne oraz ich otoczenie w celu określenia presji urbanizacyjnej na danym obszarze. Określono frekwencję występowania poszczególnych gatunków płazów oraz ich liczebność. Ogółem na obszarze badań stwierdzono 12 gatunków płazów (w tym jednego mieszańca hybrydogenetycznego). Z uwagi na problemy z oznaczeniem żab zielonych, do większości analiz wyników połączono je w jedną grupę. Najwyższą frekwencję w granicach administracyjnych Białegostoku wykazały: żaby zielone (66,6%), żaba trawna (65,5 %) i żaba moczarowa (49,4%). Są to gatunki, które występują na terenie całego miasta. Do najrzadszych gatunków płazów, obserwowanych tylko na peryferiach Białegostoku, zaliczyć można: traszkę grzebieniastą (2,3%) i ropuchę paskówkę (3,4%). Uważana za gatunek odporny na presję urbanizacyjną ropucha zielona również wykazała stosunkowo niską frekwencję (9,2%), a jedynie 22,2% wszystkich jej stanowisk rozrodczych znajdowało się w centrum miasta.
Bibliogr. s. 255-257
S. 245-264 : il. ; 25 cm
Streszcz. pol. Nazwy taksonów również łac.
Keywords: Płazy-- populacje -- Polska -- Białystok (region) [KABA]; Płazy -- skutki działalności człowieka -- Polska -- Białystok (region) [KABA]; Zwierzęta miast -- Polska -- Białystok (region) [KABA]; Amphibia; stanowiska rozrodzcze

Parasites and pathogenes in population of chaffinch Fringilla coelebs from Masurian Lakeland, NE Poland - Gryczyńska-Siemiątkowska, Alicja; Dolnik, Olga; Pawełczyk, Agnieszka; Mazgajski, Tomasz D.; Siemiątkowski, Marek (Muzeum i Instytut Zoologii PAN, 2000)
The aim of the study was to contribute the knowledge about the coincidence and species selectivity of bird parasites. The subject of our study were Chaffinches captured in Masurian Lake region (NE Poland) from 1996 to 1998. Each bird caught was visually examined for the presence of ticks. Birds' droppings and small volumes of birds' blood were collected in order to ascertain the presence of coccidia and blood parasites. Additionally the presence of bacteria Borrelia burgdorferi - the causative agent of Lyme borreliosis in birds' blood was measured with the nested-polymerase chain reaction method. In total amount of 225 Chaffinches were captured. 44% of them were infested by ticks belonging to Ixodes ricinus species (larvae and nymphs) only. Coccidia from genus Isospora were found in 80% (n = 35) of birds. Protozoans from genus Haemoproteus were ascertained in 53% (n = 59) of Chaffinches and bacteria B. burgdorferi was found in 12.7% (n = 166) of the birds. Three groups of parasites (I. ricinus, Isospora sp., Haemoproteus sp.) were found together in 26% (n = 38) of Chaffinches whereas only 5% of the birds had no parasite infection.
Referat wygłoszony na Second Meeting of the European Ornithologists' Union
Bibliogr. s. 82
S. [79]-83 ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Keywords: Zięba zwyczajna -- pasożyty -- Polska -- Mazurskie, Pojezierze -- konferencje [KABA]; Jezioro Łuknajno (okolice); Borrelia burgdorferi; łuszczaki; ptaki; Fringilla coelebs; Fringillidae; Aves; 1996-98

Sukces lęgowy dziuplaków - efekt charakterystyki miejsc gniazdowych i strategii unikania drapieżników - Mazgajski, Tomasz D. (Centrum Badań Ekologicznych PAN, 2009)
Strony 159-183 : ilustracje ; 24 cm
Bibliografia na stronach 176-182
Streszczenie w języku angielskim
Keywords: dziuplaki; sukces lęgowy; rozród; gniazda; dziuple; przeżywalność; drapieżniki gniazdowe; presja drapieżników

Does the Great Spotted Woodpecker Dendrocopos major select holes for roosting? - Mazgajski, Tomasz D. (Polish Academy of Sciences. Institute of Ecology. Publishing Office, 2002)
Characteristics of Great Spotted Woodpecker roosting holes are compared with those used for breeding. Neither postbreeding nor winter roosting holes differed from woodpecker nests with respect to tree species. condition, girth at breast height, cavity height or cavity direction. However, behavioural observations suggested that particular holes might be selected, probably in connection with microclimate condition and predator avoidance.
Strony 99-103 ; 27 cm
Bibliografia na stronie 103
Keywords: Dendrocopos major; primary cavity nesters; roosting

Nest-site characteristic of Great Spotted Woodpecker Dendrocopos major in central Poland - Mazgajski, Tomasz D. (Polish Academy of Sciences. Institute of Ecology. Publishing Office, 1998)
The study was carried out in two nature reserves in Warsaw (central Poland) in 1992-1995. Following aspects of Dendrocopos major nest hole's localisation are describing: tree species, height above the ground, tree trunk girth, condition of tree, tree fragrnent (in which nest was located) and entrance's exposure. Near all nest's parameters were different between two study areas what suggest that Great Spotted Woodpecker is quite indiscriminate in nest site selection.
Strony 33-41 : ilustracje ; 27 cm
Bibliografia na stronach 40-41
Keywords: Great Spotted Woodpecker; Dendrocopos major; nest-site; breeding; primary cavity nesters

VIII Europejski Kongres Ekologiczny EURECO '99 (Porto Carras, Grecja, 18-23 IX 1999 r.) - Mazgajski, Tomasz D. (Oficyna Wydawnicza Instytut Ekologii PAN, 2000)
Strony 151-154 ; 24 cm
Keywords: ekologia; konferencje

Effect of Old Nest Material on Nest Site Selection and Breeding Parameters in Secondary Hole Nesters — a Review - Mazgajski, Tomasz D (Museum and Institute of Zoology, Polish Academy of Sciences, 2007)
Hole nesting birds, due to the long lasting nature of cavities, use their nest sites for many years. Therefore, they may face the problem of the presence of nest material from previous breeding seasons. For a long time, the problem of old nest presence was not addressed in studies of this group of birds because nestboxes, a useful tool in studies of hole nesters, were cleaned by investigators, with old nests removed before each breeding season. In this review, the available results of experiments related to the effects of old nests on hole nesting birds are collected, recapitulated and discussed. The possible effects of old nests on nest site choice and breeding parameters, such as phenology, clutch size, fledging condition, as well as on ectoparasite numbers in a new nest, are presented. The findings show that studies on the problem of old nests started to be conducted mainly in the early 1990's, and to date more then thirty papers have been published related to this topic. The most frequent subjects of such studies in Europe were the Pied Flycather Ficedula hypoleuca, Blue and Great Tits Cyanistes caeruleus, Parus major, and European Starling Sturnus vulgaris, while in North America — the House Wren Troglodytes aedon and Eastern Bluebird Sialia sialis. The analysis of existing papers reveals that a majority of studies did not find any significant effect of old nest presence on nest site selection. In most papers, the presence of old nests did not influence birds' breeding parameters. Worse reproductive output in nestboxes containing old nests was found very rarely, and in particular seasons or study areas. Data on ectoparasite occurrence in relation to the presence of old nest material were presented only in a few papers. Fewer fleas were found in new nests built in artificially cleaned sites compared to sites containing old nests. The abundance of mites and blow fly larvae was not related to nestbox treatment. The results of this review suggest that there is no clear pattern of effects of old nest presence on hole nesters' breeding. It seems that the location of the study area, which influences the time available for birds' reproduction, is especially important for migratory species, and the impact of the ectoparasites dominating in a given study area may influence obtained results. This paper also suggests the direction of future work in this topic. Of most importance are studies carried out in natural tree holes, as the decomposition rate of old nest material could be much higher in such cavities than in nestboxes, and studies providing detailed descriptions of the costs and benefits of nest site cleaning behaviour of the birds themselves.
pg(s) 1–14
Keywords: cavity nesters; hole nesting birds; old nests; nest site cleaning behaviour; reuse; ectoparasites; nestboxes; dziuplaki wtórne

VII Międzynarodowy Kongres Ekologiczny (Florencja, 19-25 VII 1998 r.) - Mazgajski, Tomasz D.; Uchmański, Janusz (Oficyna Wydawnicza Instytut Ekologii PAN, 1999)
Strony 62-66 ; 24 cm
Keywords: ekologia; konferencje

Bird casualties on European roads - a review - Erritzoe, Johannes (1934– ); Mazgajski, Tomasz D.; Rejt, Łukasz (Museum & Institute of Zoology, 2003)
Road traffic affects the natural environment in numerous ways. The most striking of these is the death of wild animals and birds as a result of collisions with moving vehicles. In this paper the available data on bird mortality on roads is reviewed. Estimates of annual mortality for some European countries (350 000 to 27 million birds), the monthly distribution of casualties, their distribution among sex and age classes, as well as the methods used in the study of this problem are presented. The species composition of birds killed in this way is compared for several countries. In western Europe sparrows and blackbirds are the species that most frequently die on the roads, but in Central and Eastern Europe not only sparrows but also corvids and barn swallows make up a high proportion of the victims. Analysis of the monthly distribution of casualties in 10 species shows this to differ between countries, probably because of the geographic variation of certain aspects of their biology (migration, breeding etc.). Several factors affecting the frequency of casualties are discussed, and some suggestions for the prevention of bird casualties are also given.
Bibliogr. s. 90-93
S. [77]-93 : il. ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Keywords: Ptaki -- skutki działalności człowieka -- Europa [KABA]; śmiertelność na drogach; możliwości zapobiegania; czynniki; Aves